Penerapan Algoritma A* (Star) Menggunakan Graph Untuk Menghitung Jarak Terpendek - Gede Wahyu Antara Dalem, Ida Bagus (LPPM STMIK STIKOM Indonesia, 2018)
Algorithm A* (Astar) is one of the algorithm that belongs to category of searching method that has information (informed searched method). This algorithm is very good as process solution path finding (way seeker). This algorithm looks for the shortest route which will be taken a starting point to the next object. Collection data technique used in this simulation is by using Algorithm A* with heuristic function. The main purpose of this research is to learn the way of work Algorithm A* in looking for the fastest, which is simulated like a condition when someone looks for route in a traffic way. This simulation gives a realistic pictures for Algorithm A* behavior in looking for shortest route.